2003
DOI: 10.1128/aem.69.7.4144-4150.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Saccharomyces cerevisiae Strain That Consumes l -Arabinose and Produces Ethanol

Abstract: Metabolic engineering is a powerful method to improve, redirect, or generate new metabolic reactions or whole pathways in microorganisms. Here we describe the engineering of a Saccharomyces cerevisiae strain able to utilize the pentose sugar L-arabinose for growth and to ferment it to ethanol. Expanding the substrate fermentation range of S. cerevisiae to include pentoses is important for the utilization of this yeast in economically feasible biomass-to-ethanol fermentation processes. After overexpression of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
215
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 234 publications
(223 citation statements)
references
References 40 publications
(30 reference statements)
4
215
0
4
Order By: Relevance
“…As demonstrated above, promising strategies are available for a further expansion of the substrate range of ethanol-producing S. cerevisiae strains, probably starting with the full optimization of the bacterial L-arabinose pathway (Becker and Boles 2003;Sedlak and Ho 2001). We are confident that a concerted, multidisciplinary effort in yeast metabolic engineering will result in rapid progress in the areas discussed in this review.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…As demonstrated above, promising strategies are available for a further expansion of the substrate range of ethanol-producing S. cerevisiae strains, probably starting with the full optimization of the bacterial L-arabinose pathway (Becker and Boles 2003;Sedlak and Ho 2001). We are confident that a concerted, multidisciplinary effort in yeast metabolic engineering will result in rapid progress in the areas discussed in this review.…”
Section: Discussionmentioning
confidence: 85%
“…In our opinion, Becker and Boles (2003) have convincingly demonstrated that the overexpression of the bacterial L-arabinose pathway is the most promising basis for constructing L-arabinose-fermenting S. cerevisiae strains. This approach circumvents the intrinsic redox imbalances associated with expression of the fungal pathway.…”
Section: L-arabinose Fermentation By S Cerevisiaementioning
confidence: 86%
See 3 more Smart Citations